Regioselective alkylation at the inner nitrogen atom of a chlorophyll-a derivative and optical properties of the synthetic N-centered stereoisomers. (16th July 2022) - Ataka, Riko; Kawamoto, Yuki; Tamiaki, Hitoshi
Abstract: Methyl pyropheophorbide- a, one of the chlorophyll- a derivatives, was regioselectively alkylated at the nitrogen atom in the inner side of its chlorin π-system to give methyl N22-alkyl-pyropheophorbide- a hexafluorophosphate. The chemical yields decreased with an increase in the alkyl size (methyl < ethyl < propyl ≈ butyl). The products were a 2:3 mixture of N22-epimers and successfully separated by high performance liquid chromatography. Although all the stereoisomers exhibited almost the same ultraviolet–visible absorption spectra in dichloromethane, their circular dichroism spectra depended on the stereochemistry at the chiral N22-position. While their Stokes shifts were comparable to the alkyl size and independent of the stereochemistry, their fluorescence emission quantum yields and lifetimes were anti-parallel to the size and dependent on the N22-chirality. Graphical abstract: Image 1 Highlights: N22-Alkylated pyropheophorbides- a were prepared from natural chlorophyll- a. The chemical yields of the N -alkylation decreased with an increase of the alkyl size. The Stokes shifts and fluorescence quenching enhanced in the same order. The synthetic N -centered epimers were successfully separated by reverse-phase HPLC. The stereochemistry controlled their circular dichroism and fluorescence emission.